Short and sweet? Structuring Humor and Morality in American Sitcoms - Shannon Wells-Lassagne (Angles)
Seinfeld (NBC, 1989-1998), perhaps the most popular sitcom of recent years, famously insisted it was a show about nothing, about the pettiest details of everyday life. Though Seinfeld remains most outspoken about its obsession with trivia, the series in fact simply exaggerated one of the founding principles of the situation comedy: its humor is rooted in the mundane nature of the everyday. This focus on minutiae extends to the very nature of its humor; from The Honeymooners (CBS, 1955-1978) to Modern Family (ABC, 2009-present), show writers have relied on quick repartee and clever one-liners to keep the audience laughing. Interestingly, the rapid-fire nature of this fundamentally domestic comedy is in marked contrast to the very serious aspects of the sitcom, the morally motivated soliloquies that intend to teach characters a lesson. The disparity of bursts of humor and extended principled soliloquies constitute the crux of this paradoxical art form, whose unity stems from its relatability (whether it be in terms of inside jokes about the American Zeitgeist or the familiarity of its characters and setting). I would like to examine this structural dichotomy, both as it was established by classic sitcoms, and as it has been redefined and subverted by more contemporary versions.